A second reckoning : race, injustice, and the last hanging in Annapolis - Seligman, Scott D. ([Lincoln, Nebraska] : Potomac Books, an imprint of the University of Nebraska Press, 2021)
A Second Reckoning tells the story of the 1917 murder that led to the last hanging in Annapolis, Maryland, and makes an appeal for posthumous justice, especially where racial prejudice may have tainted a case.
Part 1. 1917. "A Love Match, Pure and Simple" -- "Aren't You Going to Come and Kiss Me?" -- "Altogether Separate and Different Lives" -- "All Annapolis Is Shocked" -- "Not the Faintest Clue, Theory, or Speculation" -- "The Woman Sherlock Holmes" -- "The More Delicate Hand of a Woman" -- "His Name Is Snowden" -- "We Have Got This Negro Dead Right" -- "A Maze of Circumstantial Evidence" -- "I Ain't Scared" -- "Guilty Men and Women Do Not Always Confess" -- "Fairer for the Man, the County, the State" -- Part 2. 1918. "Most Heinous and Diabolical" -- "Could Not Have Come from a White Person" -- "It Was Ten Minutes after Eleven When I Got Up" -- "The Man Shoved a Gun against My Head" -- "The Homes of White Women Must Be Protected" -- "Defending Snowden Is Defending the Black People of Maryland" -- "We Have Found No Reversible Error" -- Part 3. 1919. "I Forgive Their False Oaths" -- "This Is No Case for Mercy" -- "You Can Appeal to Me until Doomsday" -- "I Could Not Leave This World with a Lie in My Mouth" -- Part 4. 2000. "Race Is All Over This Case" -- Part 5. 2001-3. "There's Great Jubilation in the Community".
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Snowden, John, -- 1890-1919 -- Trials, litigation, etc; Snowden, John, -- 1890-1919 -- Trials, litigation, etc; Trials (Murder) -- Maryland -- Baltimore County -- 20th century; Hanging -- Maryland -- Baltimore County -- 20th century; Discrimination in criminal justice administration -- United States -- History; African Americans -- Civil rights -- History; Pardon -- United States; Evidence, Circumstantial -- United States; United States -- Race relations -- History; Discrimination dans l'administration de la justice pénale -- États-Unis -- Histoire; Noirs américains -- Droits -- Histoire; Preuve circonstancielle -- États-Unis.; États-Unis -- Relations raciales -- Histoire; Procès (Meurtre) -- Maryland -- Baltimore (Comté) -- 20e siècle.; Pendaison -- Maryland -- Baltimore (Comté) -- 20e siècle.; African Americans -- Civil rights; Discrimination in criminal justice administration; Evidence, Circumstantial; Hanging; Pardon; Race relations; Trials (Murder); Maryland -- Baltimore County; United States; 1900-1999; History; Trials, litigation, etc